Pengaruh Holding Time dan media pendingin pada proses quenching terhadap kekerasan dan kekuatan Impact pegas daun sebagai alternatif pengganti pisau slicer penuai tebu - Indratmoko, Andreas Luki; Nugroho, Eko; Asroni, Asroni; Budiyanto, Eko (Universitas Muhammadiyah Metro, 2020)
In the process of harvesting sugarcane at a sugar factory, the Sugarcane Harvester is a tractor used to harvest sugarcane equipped with a slicer knife. Nowadays slicers are still imported from abroad, and the availability is scarce and the price is still expensive. One of the efforts to find an alternative to the slicer is to use leaf springs by hardening the metal through a heat-treatment process. Namely the process of heating steel to temperatures above the critical area followed by rapid cooling called quenching. The purpose of this study was to determine the effect of holding time and the effect of cooling media on the hardness and impact strength of leaf springs and to determine the ideal holding time and the most optimal cooling media to increase the hardness and impact strength of leaf springs. As for the research method, the spring leaves were heat-treated with a temperature of 8500 C for 30 minutes and 60 minutes and then cooled using oil, saltwater, and water as media. The method used is observation, literature study, testing, and documentation. The results obtained from this study were at a temperature of 8500 C with a holding time of 30 minutes the best hardness value was 477 VHN and 0.42% increase, the best impact strength value was 0.03433 J / mm2 and 87.71% decrease, and the two cooling media, namely oil. At a temperature of 8500C with a holding time of 60 minutes the best hardness value was 534 VHN and 12.42% increase, the best value of impact strength was 0.03203 J / mm2 and 88.53% decrease, and the two cooling media were oil as well. So that oil is the most optimal medium for changing the mechanical properties of the Sugarcane Harvester slicer because the oil can carry a carbon layer from the cooling process that takes place and the cooling rate of the oil is not too fast from the cooling media of brine and water because of its viscosity. Keywords: Holding Time, Cooling Media, Hardness, Impact Strength, Quenching, Leaf Spring, Slicer.